Collective action in a polycentric water governance system. (29th August 2018) - Baldwin, Elizabeth; McCord, Paul; Dell'Angelo, Jampel; Evans, Tom
Abstract: Small‐scale irrigation systems are important for agricultural productivity in dryland agroecosystems, particularly in areas where there is significant intra‐ and interannual changes in rainfall patterns. Institutional analysis of common‐pool resources has demonstrated the principles that tend to result in sustained water governance systems. However, previous work did not fully articulate the nested nature of institutions and how polycentric arrangements can play a role in both the formation and the ongoing maintenance of these governance systems. To better understand collective action across water user groups and decision‐makers at multiple governance levels, we undertake a multilevel analysis of Kenya's polycentric approach to water governance, in place since reforms were initiated in 2002. Survey and interview data indicate that in the postreform period, water users in Kenya's Upper Ewaso Ng'iro basin engaged in behaviors associated with collective action, including reduced water use by upstream users to address downstream users' needs. We examine the factors that promote collective action in the region, asking whether features associated with polycentric governance have helped to promote collective action. We find that the presence of multiple decision centers with overlapping authority over water governance functions creates necessary—but not sufficient—conditions for collective action to occur. Regulations and formal conflict resolution mechanisms provide incentives for water users to cooperate, while shared membership in regional Water Resource Users Associations facilitates informal opportunities for users to share information and build trust over time.